(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article develops and evaluates three structural transformation scenarios - inertial, reform, and innovation - for Kashkadarya Region’s industrial sector over the 2025–2030 horizon, based on System GMM dynamic panel estimates and integrated scenario analysis. The empirical model, estimated on panel data from 148 enterprises (2018–2023), identifies digitalisation investment, export activity, cluster policy participation, and energy efficiency as statistically significant determinants of total factor productivity. The innovation scenario, premised on full implementation of the proposed structural optimisation mechanism, projects industrial output growth from UZS 18,400 billion (2024) to UZS 42,000 billion (2030), a reduction of the Herfindahl–Hirschman Index from 2,840 to 1,450, and an increase in the IT sector share from 2.3% to 8.6%. A KPI monitoring system and risk matrix provide an adaptive governance framework for scenario implementation.